Increased Efficiency of Exogenous Messenger RNA Translation in a Krebs Ascites Cell Lysate - Metafora, S. (1972)
Addition of a 0.5 M KCl wash fraction from rabbit reticulocyte ribosomes causes a 3- to 10-fold increase in the extent of translation of natural mRNAs by Krebs-cell lysates. In the presence of the wash fraction, 1 pmol of rabbit or mouse 10S RNA directs the incorporation of 80 pmol of leucine into rabbit globin. The addition of human 10S RNA results in the synthesis of equal amounts of human α and β chains, identified by column chromatography. The stimulation by the wash fraction is almost completely dependent on added mammalian tRNA. In contrast to the wash fraction from rabbit reticulocytes, the wash fraction isolated from Krebs-cell ribosomes is inhibitory to both endogenous and exogenous mRNA translation. The stimulation by the wash fraction from rabbit ribosomes is not specific for globin mRNAs, but also increases endogenous, phage Qβ, and viral RNA-directed protein synthesis.